ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 1 PADANG DITINJAU DARI GAYA KOGNITIF - FIKRIYATUL Khairat (Departemen Matematika, 2019)
This research aims to describe the student’s mathematical critical thinking ability trough the field dependent (FD) or field independent (FI) kognitive styles. This research used mixed research to describe the relation between two variabels with statistics approach and descriptive qualitative approach. Data was taken from 168 students of SMP Negeri 1 Padang and choose 6 of them to be interviewed. The result of data analysis showed that there is a significant correlation between kognitive styles and student’s mathematical critical thinking ability. The student with FD cognitive styles showed a higher ability than student with FI cognitive style in identify the asumptions needed to solve mathematical problem. Both of kognitive styles show the equal ability in indentify data that is relevant to the mathematics problem given. Otherwise, the student with FI cognitive styles showed a higher ability than student with FD cognitive style in examining the truth of the statement, compiling questions, and solving mathematical problems.Keywords—critical thinking, mathematical critical thinking ability, cognitive styles, field dependent, field independent